a: \(\dfrac{x}{7}=\dfrac{y}{13}\)
mà x+y=40
nên Áp dụng tính chất của dãy tỉ số bằng nhau, ta được:
\(\dfrac{x}{7}=\dfrac{y}{13}=\dfrac{x+y}{7+13}=\dfrac{40}{20}=2\)
=>\(x=2\cdot7=14;y=2\cdot13=26\)
b: \(\dfrac{x}{19}=\dfrac{y}{21}\)
mà 2x-y=34
nên Áp dụng tính chất của dãy tỉ số bằng nhau, ta được:
\(\dfrac{x}{19}=\dfrac{y}{21}=\dfrac{2x-y}{2\cdot19-21}=\dfrac{34}{17}=2\)
=>\(x=2\cdot19=38;y=2\cdot21=42\)
c: \(\dfrac{x}{y}=\dfrac{17}{3}\)
=>\(\dfrac{x}{17}=\dfrac{y}{3}\)
mà x+y=-60
nên Áp dụng tính chất của dãy tỉ số bằng nhau, ta được:
\(\dfrac{x}{17}=\dfrac{y}{3}=\dfrac{x+y}{17+3}=\dfrac{-60}{20}=-3\)
=>\(x=-3\cdot17=-51;y=-3\cdot3=-9\)
d: \(\dfrac{x}{4}=\dfrac{y}{7}\)
mà x+y=110
nên Áp dụng tính chất của dãy tỉ số bằng nhau, ta được:
\(\dfrac{x}{4}=\dfrac{y}{7}=\dfrac{x+y}{4+7}=\dfrac{110}{11}=10\)
=>\(x=10\cdot4=40;y=7\cdot10=70\)
e: \(\dfrac{x}{y}=\dfrac{7}{8}\)
=>\(\dfrac{x}{7}=\dfrac{y}{8}\)
mà x+y=90
nên Áp dụng tính chất của dãy tỉ số bằng nhau, ta được:
\(\dfrac{x}{7}=\dfrac{y}{8}=\dfrac{x+y}{7+8}=\dfrac{90}{15}=6\)
=>\(x=6\cdot7=42;y=6\cdot8=48\)
f: 2x=9y
=>\(\dfrac{x}{9}=\dfrac{y}{2}\)
mà y-x=49
nên Áp dụng tính chất của dãy tỉ số bằng nhau, ta được:
\(\dfrac{x}{9}=\dfrac{y}{2}=\dfrac{y-x}{2-9}=\dfrac{49}{-7}=-7\)
=>\(x=-7\cdot9=-63;y=-7\cdot2=-14\)
g: \(\dfrac{x}{4}=\dfrac{y}{8}\)
=>\(\dfrac{x}{1}=\dfrac{y}{2}\)
mà x+y=55
nên Áp dụng tính chất của dãy tỉ số bằng nhau, ta được:
\(\dfrac{x}{1}=\dfrac{y}{2}=\dfrac{x+y}{1+2}=\dfrac{55}{3}\)
=>\(x=\dfrac{55}{3}\cdot1=\dfrac{55}{3};y=\dfrac{55}{3}\cdot2=\dfrac{110}{3}\)
h: \(\dfrac{x}{8}=\dfrac{y}{3}\)
mà x-y=35
nên Áp dụng tính chất của dãy tỉ số bằng nhau, ta được:
\(\dfrac{x}{8}=\dfrac{y}{3}=\dfrac{x-y}{8-3}=\dfrac{35}{5}=7\)
=>\(x=7\cdot8=56;y=3\cdot7=21\)